2020
DOI: 10.1021/acscombsci.0c00001
|View full text |Cite
|
Sign up to set email alerts
|

Immobilized Carbodiimide Assisted Flow Combinatorial Protocol to Facilitate Amide Coupling and Lactamization

Abstract: Through a screen of over one hundred and 30 permutations of reaction temperatures, solvents, carbodiimide resins, and carbodiimide molar equivalences, in the presence, absence, or combination of diisopropylamine and benzotriazole additives, a convenient and first reported carbodiimide polymer-assisted flow approach to effect amide coupling and lactamization was developed. The protocol entails injecting a single solution (1:9 dimethylformamide: dichloromethane) containing a carboxylic acid and an amine or linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…Nonetheless, through reductions of flow rates and increases in reaction column temperature (1.0-0.2 mL min À 1 , 40-140 °C, entries 1-4 and 5-9, respectively), conversions of 3 to amide 2 increased considerably to near 70%. Further, whilst varying the continuous flow solvent to toluene, tetrahydrofuran (THF), acetonitrile (ACN), and N,Ndimethylformamide (DMF) proved detrimental (i. e. < 10-58%, entries [10][11][12][13], the use of chloroform (CHCl 3 ) promoted an incremental increase in the conversion to 2 (74%, entry 14). Additionally, the absence or variation of base from Et 3 N to DIPEA or DMAP, and altering the activating agent from BrCCl 3 to trichloroacetonitrile (CCl 3 CN), imparted a minimal decrease to the affordance of 2 (66-70%, entries 15-18).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, through reductions of flow rates and increases in reaction column temperature (1.0-0.2 mL min À 1 , 40-140 °C, entries 1-4 and 5-9, respectively), conversions of 3 to amide 2 increased considerably to near 70%. Further, whilst varying the continuous flow solvent to toluene, tetrahydrofuran (THF), acetonitrile (ACN), and N,Ndimethylformamide (DMF) proved detrimental (i. e. < 10-58%, entries [10][11][12][13], the use of chloroform (CHCl 3 ) promoted an incremental increase in the conversion to 2 (74%, entry 14). Additionally, the absence or variation of base from Et 3 N to DIPEA or DMAP, and altering the activating agent from BrCCl 3 to trichloroacetonitrile (CCl 3 CN), imparted a minimal decrease to the affordance of 2 (66-70%, entries 15-18).…”
Section: Resultsmentioning
confidence: 99%
“…[5a] Moreover, we have previously observed PS-carbodiimide regeneration to be problematic, returning low conversions of the active carbodiimide coupling species. [10] On the other hand, the successful recycling of both the PS-triphenylphosphine-based (PS-PPh 3 ) [11] and benzotriazole-based (PS-HOBt) [8d,f] reagents has been described on prior occasions. Additionally, it is reported that the respective employment of both PS-PPh 3 and PS-HOBt, in concert with flow-based processing, can deliver tangible benefits to both reaction efficiency and protocol practicability.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the removal of excess materials, the release of final products, and even reagent regeneration by continuous flow are inherently more efficient than standard mixing strategies [6a,7] . As each of these procedures can be sequentially performed in‐line, flow methods can also minimise physical handling requirements [6a,8] . Moreover, these processes can all be monitored through spectrophotometric analysis of the elution stream [7–8] …”
Section: Introductionmentioning
confidence: 99%
“…As each of these procedures can be sequentially performed in‐line, flow methods can also minimise physical handling requirements [6a,8] . Moreover, these processes can all be monitored through spectrophotometric analysis of the elution stream [7–8] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation